Efeito da valência emocional na leitura em português brasileiro: evidências de movimentação ocular - Santos, Willamy Matos dos (2025)
This dissertation presents an investigation into the effects of emotional valence on reading processing in Brazilian Portuguese. Based on theories of emotional processing (Barrett, 2017; Damásio, 2018; LeDoux, 1996; Phillips et al., 2003) and reading (Rayner, 1998), we seek to understand how texts with different affective charges influence reading, using eye-tracking as a methodology. To this end, we start from the hypothesis that different affective charges attributed to texts can interfere with both reading fluency and textual comprehension. Specifically, we assume that texts with emotional content generate distinct effects on reading behavior compared to neutral texts. This assumption is based on the idea that the presence of emotions in texts can modulate readers' attention, emotional engagement, and cognitive processing (Megalakaki, Ballenghein & Baccino, 2019). The methodological approach involved three stages: analysis of the lexical frequency of the stimuli, validation of the emotional valence attributed to the texts, and, finally, the main experiment with eye tracking. Thirty-eight university students, native speakers of Brazilian Portuguese, participated in the main experiment. The readers were exposed to 18 short, previously validated texts with positive, negative, or neutral valence and answered comprehension questions after each text. Eye movement measures such as first fixation duration, total gaze duration, number of fixations, number of regressions, and response accuracy were analyzed. The results suggest that, although emotional valence did not significantly influence first fixation time, there was a higher number of fixations on neutral texts. Trends in continuous reading measures suggest that texts with emotional content were processed more fluently. Despite this, neutral texts resulted in greater accuracy on comprehension questions. These findings suggest that emotion can favor reading pace, but that its interference in comprehension depends on the type of information requested, the emotional intensity of the stimulus and the degree of cognitive engagement required by the task.